AN IN VITRO STUDY OF ANTIOXIDANT CAPACITY AND RADICAL SCAVENGING EFFECT OF SPINACIA OLERACEA LEAF EXTRACT - C Damle, Mrinalini; K Jadhav, Shivani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was carried out to evaluate the preliminary phytochemical screening and antioxidant activity of ethanolic extract of Spinacia oleracea (SO). Methods: The leaves of SO were shade dried, and the extract was prepared using solvent ethanol by Soxhlet extraction method. The preliminary phytochemical screening was carried out on the leaf extract of the plant. The total phenolic content and total flavonoids were estimated using Folin- Ciocalteu's and aluminum chloride reagents, respectively. Antioxidant activities were studied using 1,1-diphenyl-2-picrylhydrazyl, nitric oxide, hydrogen radical, lipid peroxidation, and phosphomolybdenum radical scavenging assays. Results: The preliminary phytochemical analysis revealed the presence of bioactive constituents such as phenols, alkaloids, flavonoids, saponins, and glycosides. As SO is a rich source of different bioactive component, it contains a considerable amount of flavonoids and phenols. The different antioxidant assays proved that spinach is one of the best antioxidants with its ability to scavenge different radicals that generate oxidative stress. Conclusion: The observed activity may be associated with bioactive components such as phenols and flavonoids present in the leaf extracts and could have greater importance as nootropic plant in oxidative stress-related degenerative diseases such as Alzheimer and dementia.